The genetics of divergence and reproductive isolation between ecotypes of Panicum hallii. Issue 1 (23rd September 2014) - Lowry, David B.; Hernandez, Kyle; Taylor, Samuel H.; Meyer, Eli; Logan, Tierney L.; Barry, Kerrie W.; Chapman, Jarrod A.; Rokhsar, Daniel S.; Schmutz, Jeremy; Juenger, Thomas E.
Summary: The process of plant speciation often involves the evolution of divergent ecotypes in response to differences in soil water availability between habitats. While the same set of traits is frequently associated with xeric/mesic ecotype divergence, it is unknown whether those traits evolve independently or if they evolve in tandem as a result of genetic colocalization either by pleiotropy or genetic linkage. The self‐fertilizing C4 grass species Panicum hallii includes two major ecotypes found in xeric (var. hallii ) or mesic (var. filipes ) habitats. We constructed the first linkage map for P. hallii by genotyping a reduced representation genomic library of an F2 population derived from an intercross of var. hallii and filipes . We then evaluated the genetic architecture of divergence between these ecotypes through quantitative trait locus (QTL) mapping. Overall, we mapped QTLs for nine morphological traits that are involved in the divergence between the ecotypes. QTLs for five key ecotype‐differentiating traits all colocalized to the same region of linkage group five. Leaf physiological traits were less divergent between ecotypes, but we still mapped five physiological QTLs. We also discovered a two‐locus Dobzhansky–Muller hybrid incompatibility. Our study suggests that ecotype‐differentiating traits may evolve in tandem as a result of genetic colocalization.